POLITIK HUKUM PEMBENTUKAN PERJANJIAN INTERNASIONAL PASCA PUTUSAN MAHKAMAH KONSTITUSI NOMOR 13/PUU-XVI/2018 (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
The ratification of an international treaty is a way for a country to declare to be bound by an international treaty. The Constitutional Court issued the Constitutional Court Decision No.13/PUU-XVI/2018 regarding the International Treaty Law which was motivated by differences of opinion regarding the process of ratifying international treaties. It is necessary to know how the impact of this Constitutional Court Decision on the process of implementing the ratification of international agreements by looking at the comparison of the practice of ratifying international agreements in various countries.  The legal politics after the decision of the case is right in the legal system regarding the application of international agreements in the national legal system. Article 2 of Law Number 24 of 2000 concerning International Treaties with Article 11 of the 1945 Constitution of the Republic of Indonesia only regulates the division of authority between the President and the House of Representatives in ratifying international treaties. The lack of clarification on the Indonesian legal and political system creates problems in the application of domestic international agreements, especially in relation to the role and authority of the House of Representatives and the President in terms of making international agreements, the absence of an explanation of the authority of the House of Representatives in terms of making international agreements has implications for various questions regarding the legal construction of the authority of the House of Representatives after the decision of the Constitutional Court number 13/PUU-XVI/2018 concerning International Agreements.Keywords: Legal Politics – International Treaties – Constitutional Court Decisions.